Job Crafting among Labor Union Representatives: Its Impact on Work Engagement and Job Satisfaction - Almer Villajos; Cristina García-Ael; Gabriela Topa (Social Sciences, 2019)
Labor Union activity still lacks recognition as an ordinary work activity. However, on the one hand, labor union representatives must deal with many tasks (internal and external) that can sometimes be overwhelming. On the other hand, given its vocational nature and the possibility that it offers for the workers themselves to organize their work, the area of trade unionism can be interesting for the study of job crafting and other phenomena associated with well-being, such as burnout or work engagement. Unfortunately, to date, there are no investigations that address these phenomena, especially job crafting in the labor union environment. Therefore, the objective of the present study is to explore the existing relationships between the job crafting of the labor union representatives and their well-being and health. A sample of 78 participants engaged in labor union activity for an average of 12.62 years completed job satisfaction and work engagement measures. The results indicate that job crafting dimensions predicted participants’ job satisfaction and engagement.